An enzyme mimic ammonium polymer as a single catalyst for glucose dehydration to 5-hydroxymethylfurfural. Issue 4 (25th February 2015) - Cao, Xueqin; Teong, Siew Ping; Wu, Di; Yi, Guangshun; Su, Haibin; Zhang, Yugen
Abstract : An ammonium resin (PBnNH3 Cl) was used as a single catalyst for the glucose and polysaccharide dehydration to 5-hydroxymethylfurfural (HMF) in high selectivity. Abstract : An ammonium resin (PBnNH3 Cl) was used as a single catalyst for the glucose and polysaccharide dehydration to 5-hydroxymethylfurfural (HMF) in high selectivity (>80%) in a DMSO or biphasic reaction system. The isomerization mechanism was also studied by using the DFT computational method.